Prosedur Pembinaan dan Pengawasan Notaris oleh Majelis Pengawas Notaris Daerah - Lia Trizza Firgitta Adhilia; Anisah Daeng Tarring (Jurnal Litigasi Amsir, 2022)
This study aims to find out and analyze the procedures regarding the Guidance and Supervision of Notaries carried out by the Notary Regional Supervisory Council, as stipulated in Law Number 30 of 2004 concerning the Position of Notary, Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 15 of 2020 concerning Procedures for Examining the Supervisory Board of Notaries, as well as Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 16 of 2021 concerning Organizational Structure and Work Procedures, Procedures for Appointment and Dismissal, as well as the Budget of the Notary Supervisory Board. This research is normative legal research using a statutory approach (statute approach) and a conceptual approach (conceptual approach). The results of the study show that the procedures for fostering and supervising notaries carried out by the Regional Notary Supervisory Board are preventive or preventative in nature, so that there is no misuse of office committed by notaries, and curative supervision and coaching, which means supervision and guidance to Notaries in carrying out their positions, The procedures for supervision and guidance are carried out by conducting periodic checks, namely at least once a year, on Notary protocols, Office Conditions, complete office administration, employees, Notary nameplates and so on, as well as inspections at certain times if deemed necessary, as well as guidance in the context of a Notary committing a violation of the code of ethics, or there is an allegation of a violation of the performance of Notary duties or a Notary who performs his/her duties not in accordance with UUJN, so that it can interfere with the implementation of the duties of his position or can even cause harm to the community.